Launch : starting a new church from scratch - Searcy, Nelson; Thomas, Kerrick (Grand Rapids : Baker Books, 2017)
"Starting a new church is a daunting task. But with the right guides, the right spirit, and the right strategies, you can build a healthy, growing church from the ground up. Sharing their story of launching The Journey Church in New York City, Nelson Searcy and Kerrick Thomas offer not just church planting theory but invaluable boots-on-the-ground experience of starting with nothing and then watching membership grow to more than a thousand people in three years. Now thoroughly revised and expanded to reflect the ever-changing landscape of church planting, Launch offers clear, practical how-to-strategies."--Back cover.
Foundation -- Formation -- Implementation.
Includes bibliographical references (page 247).
Keywords: Church development, New